School based versus supplemental vaccination strategies in the delivery of vaccines to 5-19 year olds in Africa - a systematic review - Haddison, Christiana Eposi (Department of Public Health and Family Medicine, 2018)
Background: Some vaccine preventable diseases still remain a public health burden in many African countries. The occurrence of vaccine preventable diseases in all age groups has led to the realization of the need to extend routine immunisation services to school age children and adolescents. Supplemental immunisation activities (SIAs) and school based vaccination (SBV) are two common strategies used to complement the EPI in vaccine delivery. Therefore, this review aimed to assess the effectiveness of SIAs compared to SBV in the administration of vaccines to 5-19 year olds in Africa. Methods and findings: Systematic review methods (protocol number CRD42017057475) were used to address our study aim. Electronic databases were searched up to March 30, 2017 for primary studies investigating the delivery of vaccines via SIAs or SBV to 5-19 year olds. To be included in the review, studies must have reported any of the following outcomes: vaccination coverage, cost of the vaccination strategy or effect of the strategy on routine immunisation. During the search, no restriction was placed on language or the study period. The search was complemented by browsing reference lists of potential studies. Out of the 4938 studies identified, 31 studies met our inclusion criteria. Both SIAs and SBV showed high vaccination coverage. This result should be interpreted with caution due to the high heterogeneity observed across the included studies. The SIAs reported a higher coverage of 91% (95% CI: 84%, 98%) than SBV which had a coverage of 75% (95% CI: 67%, 83%). In most settings, SBV was reported to be more expensive than SIAs. The SIAs were found to negatively affect routine immunisation services. Conclusions: Both SIAs and SBV are routinely used to complement the EPI in the delivery of vaccines in Africa. In settings where school enrolment is suboptimal as is the case in many African countries, our results show SIAs may be more effective in reaching school age children and adolescents than SBV. The SBV has only been tested in the delivery of two or three dose HPV vaccine to adolescent girls, whereas SIAs have been tested in the delivery of different types of vaccines. Our results re-iterate the importance of systematic evidence to best inform African authorities on the optimal delivery strategies of vaccines targeting school age children and adolescents into their immunisation programme.